Faktor-Faktor Yang Menghambat Penyelesaian Sengketa Tanah Waris Akibat Pemalsuan Surat Wasiat Melalui Pengadilan Negeri (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
Land disputes are civil disputes that are often filed by justice seekers in the District Court. Recently, many inheritance disputes often occur in families, the inheritance in question is in the form of movable and immovable property. This research aims to determine the process of resolving inheritance land disputes due to falsification of wills in district court and the inhibiting factors which are useful as a reference. The type of research used is empirical research, by interviewing plaintiffs, defendants and co-defendants in case decision no. 44/Pdt.G/2011/PN.Gtlo.The results of the research show that resolving inheritance land disputes resulting from forgery of wills through the District Court is preferred as a solution because it is an institution that provides the justice desired by the plaintiff and its decisions have permanent legal force. Inhibiting factors found in the research process, namely internal and external factors. Internal factors consist of lack of human resources, administrative services, and lack of facilities. And external factors consist of cost, time, good faith, lack of understanding of the parties, chaos in the trial, and lack of evidence.